Dasycerine rove beetles: Cretaceous diversification, phylogeny and historical biogeography (Coleoptera: Staphylinidae: Dasycerinae) - Yin, Zi-Wei; Lu, Liang; Yamamoto, Shuhei; Thayer, Margaret K.; Newton, Alfred F.; Cai, Chen-Yang （蔡晨阳） (Cladistics, 2020)
Within the hyperdiverse beetle family Staphylinidae, Dasycerinae is one of the smallest and most cryptic subfamilies, comprising a sole extant genus characterized by a latridiid beetle-like body form. Little has been known about their early diversification, character evolution, phylogeny and historical biogeography because of limited fossil material and lack of a phylogeny integrating extant and extinct representatives. Here we report an unexpectedly diverse dasycerine fauna from the mid-Cretaceous of northern Myanmar, including a new genus and four new species. To reconstruct the early evolutionary history of Dasycerinae, we present a phylogenetic framework of the subfamily based on a dataset integrating all extant and extinct taxa using parsimony, maximum-likelihood and Bayesian methods. dagger Cedasyrusgen. n., characterized by distinct sexual dimorphism in antennal and elytral lengths, is recovered as the basal-most lineage, sister to the remaining two extinct genera and all livingDasycerusspecies. dagger Vetudasycerusis recovered as sister to dagger Protodasycerus + Dasycerus. Among all extinct taxa, dagger Protodasycerusbears distinctly longer elytra, and appears to represent a transitional form from dagger VetudasycerustoDasycerus. Phylogenetic inferences and ancestral distribution reconstruction support an "Out-of-Orient" model for Dasycerinae. Either the Bering- or North Atlantic Land Bridge may have served as a passageway for dasycerine dispersal between Eurasian and North American continents. An elevation-reconstruction analysis indicated that the ancestor of the extantDasycerusprobably lived at a high altitude and stayed at this elevation through the end of the Miocene. We propose that the extinction of dasycerine ancestors living on the Tethyan islands at low altitude was likely caused by sea-level rise and climatic warming during the Late Cretaceous. The high-altitude areas might have played the role of refugia that harboured subalpine derivatives which eventually gave rise to the extantDasycerus.